دور الوسائل التعليمية في زيادة عملية الادراك دراسة ميدانية على عينة من تلاميذ الطور الابتدائي بولاية الأغواط - نجاة مشري; تومية شقنان; عطا الله بن يحي (My University, 2022)
The study titled The Role of Using Cognitive techniques in the Students’ Learning Process. The two researchers used a descriptive exploratory approach, and it has been applied in primary schools in the wilaya of Laghouat during a time bounded period (from February to August 2021). The variables consisted of students from second, third, fourth, and fifth grade in the primary schools. Observation network has been used as a tool as well. The study hypothesized that:  There is a relation between the usage of teaching techniques and the level of understanding  The current teaching resources used in educational institutions shows a major lack in using techniques and shortage of motivation from the teachers in teaching methods.